UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH - Engkar, Engkar (LPPM Universitas Bina Bangsa, 2024)
The implementation of learning in elementary schools must be able to use real learning media so that it can improve the learning process carried out by teachers. Through problem-based learning, teachers provide the potential for students to be active and understand material in the real world. The research approach used in this research is a quantitative and qualitative approach because it aims to describe the implementation of a problem-based learning model to increase motivation and learning outcomes in junior high school mathematics. The type of research carried out is classroom action research (PTK). The research was carried out at SDN Pasiripis 1, Majalengka Regency. This research was carried out over 2 cycles and was carried out during July 2023. The results of data analysis show that the use of the problem-based learning model properly implemented at SDN Pasiripis I was able to improve student learning outcomes and student learning motivation. This can be seen in the improvement of student activities in the learning process at each cycle